Secondary primary tumor mimicking osteoradionecrosis - Giovanna Lopes Carvalho,; Daniele Heguedusch,; Antônio Cássio Assis Pellizzon,; Renan Bezerra Lira,; Fábio Abreu Alves,; Graziella Chagas Jaguar, (Autopsy and Case Reports, 2022)
Nasopharyngeal carcinoma (NPC) is a malignant tumor rarely found in the head and neck, representing about 1% of all malignancies. The main treatment for NPC is radiation therapy, which is often given in combination with chemotherapy. However, such treatment may lead to long‐term complications, including second primary tumors (SPTs) and osteoradionecrosis (ORN). Both complications have similar radiological characteristics, which can lead to erroneous diagnoses. This paper describes a case of a second primary tumor in a patient after 20 years of radiotherapy in the area where a previous extraction was performed, mimicking an osteoradionecrosis process.